Single-cell RNA sequencing analysis reveals cell landscape and gene signatures associated with granulomatous lobular mastitis - Wang, Junyue; Zeng, Yifei; Wang, Mengjie; Zhang, Dongxiao; Zhang, Xulong; Liu, Min; Li, Yudong; Xu, Xiaolong (Frontiers in Immunology, 2025)
BackgroundGranulomatous lobular mastitis (GLM) is a refractory chronic inflammatory breast disease characterized by granuloma formation and recurrent abscesses, yet its molecular pathogenesis remains poorly understood. To address this knowledge gap, we aimed to systematically compare the immune microenvironment between GLM and healthy breast tissues, reveal disease-associated cellular subpopulations, and characterize key dysregulated genes and pathways driving GLM pathogenesis.MethodsWe performed single-cell RNA sequencing (scRNA-seq) on breast tissue samples from 3 patients with GLM and 3 healthy controls. The sequencing data were subjected to cell clustering, cell abundance comparison, and differential gene analysis to assess immune microenvironment differences. We performed macrophage subtyping and revealed differentially expressed genes. Using GO/KEGG analysis, we characterized signaling pathway disparities in M1 macrophages to investigate potential pathogenic mechanisms.Results11 major cell types were detected through scRNA-seq. In GLM tissues, immune cell infiltration was significantly increased (P < 0.05), with macrophages and neutrophils showing predominant infiltration. Macrophages were further classified into M1, M2a, M2b, and M2c subtypes, with M1 being the most predominant. In M1 macrophages, we observed marked upregulation of: FCGR1A (CD64), CYBB and NCF1 (core NADPH oxidase components), TNFSF10 (TRAIL). Cytokine signaling and phagocytosis-related pathways were significantly enriched in M1 macrophages.ConclusionTo our knowledge, this is the first scRNA-seq study of GLM, identifying 11 major cellular populations and implicating macrophages—especially M1 subtype—as central to disease immunopathology. We report dysregulated expression of CD64, NADPH oxidase components, and TRAIL, prompting the hypothesis that phagocytic function may be impaired and nominating this axis as a potential therapeutic target.